Chromatographic Separation of Isomaltooligosaccharides on Ion-Exchange Resins: Effect of the Cationic Form - M.C. Rabelo; C.S.M. Pereira; S. Rodrigues; A.E. Rodrigues; D.C.S. Azevedo (Adsorption Science & Technology)
Prebiotic isomaltooligosaccharides (IMOs) are composed of α-d-glucose units linked by glucosidic α (1Ø6) bonds and they remain intact until reaching the large bowels, where they are metabolized by bifidobacteria and lactobacillus. These saccharides can also be synthesized enzymatically, wherein the reaction media is composed of monosaccharides (glucose and fructose), disaccharides (sucrose and maltose), IMOs (the product of interest) and dextrans. Dextrans are readily separated by solvent precipitation; however, continuous chromatographic separation (simulated moving bed or SMB) should be an interesting option for the enrichment and purification of IMOs from mono- and disaccharides. The objective of the present work was to measure fundamental adsorption data of IMOs, mono- and disaccharides in preparative columns packed with ion-exchange resin of different cationic forms (K + , Ca + , H + and Na + ), so as to verify the influence of the cation on the selectivity and capacity. Ion exchange in H + form showed the best performance in terms of selectivity between maltose and maltotriose, but the resin in the K + form had superior adsorption capacities. Additionally, on the basis of equilibrium theory, optimal SMB operating conditions for resin H + will yield the highest productivity as compared with the other cationic forms.